The Macklin effect: pneumomediastinum and pneumopericardium following blunt chest trauma - Baharudin , Abdullah; Razali, Mohd Sayuti; Shahid, Hassan (Malaysian Medical Associations, 2006)
Pneumomediastinum, also known as mediastinal emphysema, is due to air collections surrounding the mediastinum. It is reported that up to 10% of patient with blunt chest trauma will develop pneumomediastinum and in less than 2% of patients, pneumomediastinum results from blunt tracheobronchial lesions1 • Pneumopericardium in adults is a rare disorder and may be seen most commonly after blunt chest trauma in combination with pneumothorax or pneumomediastinum 2.